Penerapan Metode Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) Dalam Mendukung Keputusan Pemberian Bantuan Uang Kuliah Tunggal - Darmeliani Sinaga; Suci Ramadhani Sihotang (ADA Research Center, 2023)
In accordance with the regulations that have been determined by the aid provider to obtain assistance, criteria are needed to determine who will be selected to receive assistance. The distribution of aid is carried out to help underprivileged or high achieving students during their studies. To help determine which students are worthy of receiving assistance, a decision support system is needed. The method used for the Decision Support System is to use the Multi-Objective Optimization Method on the basis of Ratio Analysis (MOORA). In this research, a case will be raised, namely looking for the best alternative based on criteria that have been determined using the MOORA method. This method was chosen because it is able to select the best alternative from a number of alternatives, in this case the alternative in question is students who are entitled to receive assistance based on specified criteria. The research was carried out by finding the weight value for each attribute, then a candidate sorting process was carried out which would determine the optimal alternative, namely the students who were entitled to receive the assistance.